Distribution of actin and tropomyosin in Cryptosporidium muris - Yu, J R (Korean journal of parasitology, 1998)
Actin and tropomyosin of Cryptosporidium muris were localized by immunogold labeling. Two kinds of antibodies for actin labeling were used. The polyclonal antibody to skeletal muscle (chicken back muscle) actin was labeled on the pellicle and cytoplasmic vacuoles of parasites. The feeder organelle has showed a small amount of polyclonal actin antibody labeling as well. Whereas the monoclonal antibody to smooth muscle (chicken gizzard muscle) actin was chiefly labeled on the filamentous cytoplasm of parasites. The apical portion of host gastric epithelial cell cytoplasm was also labeled by smooth muscle actin together. The polyclonal antibody to tropomyosin was much more labeled at C. muris than host cells, so it could be easily identified even with low magnification (x2,000). The tropomyosin was observed along the pellicle, cytoplasmic vacuoles, and around the nucleus also. The skeletal muscle type actin seems to play a role in various cellular functions with tropomyosin in C. muris; on the other hand, the smooth muscle type actin was located mainly on the filamentous cytoplasm and supported the parasites' firm attachment to host cells. Tropomyosin on the pellicle was thought to be able to stimulate the host as a major antigen through continuous shedding out by the escape of sporozoites or merozoites from their mother cells.